Mitigation needs adaptation: tropical forestry and climate change - Guariguata, Manuel R.; Cornelius, Jonathan P.; Locatelli, Bruno; Forner, C.; Sánchez Azofeifa, G.A. (2008)
The relationship between tropical forests and global climate change has so far focused on mitigation, while much less emphasis has been placed on how management activities may help forest ecosystems adapt to this change. This paper discusses how tropical forestry practices can contribute to maintaining or enhancing the adaptive capacity of natural and planted forests to global climate change and considers challenges and opportunities for the integration of tropical forest management in broader climate change adaptation. In addition to the use of reduced impact logging to maintain ecosystem integrity, other approaches may be needed, such as fire prevention and management, as well as specific silvicultural options aimed at facilitating genetic adaptation. In the case of planted forests, the normally higher intensity of management (with respect to natural forest) offers additional opportunities for implementing adaptation measures, at both industrial and smallholder levels. Although the integration in forest management of measures aimed at enhancing adaptation to climate change may not involve substantial additional effort with respect to current practice, little action appears to have been taken to date. Tropical foresters and forest-dependent communities appear not to appreciate the risks posed by climate change and, for those who are aware of them, practical guidance on how to respond is largely non-existent. The extent to which forestry research and national policies will promote and adopt management practices in order to assist production forests adapt to climate change is currently uncertain. Mainstreaming adaptation into national development and planning programs may represent an initial step towards the incorporation of climate change considerations into tropical forestry.